Spontaneous closure of an iatrogenic coronary artery fistula during recanalization of a chronic total occlusion lesion: A case report. Issue 3 (January 2019) - Yu, Xue; Wang, Xinyue; Zhang, Ruisheng; Xu, Feng; Ji, Fusui
Abstract: Rationale: Coronary perforation leading to fistula directed to the right ventricle is a rare complication of percutaneous coronary intervention (PCI). The reported outcomes vary from a stable state to rapid deterioration. Patient concerns: An 86-year-old man was diagnosed with non-ST elevation myocardial infarction, and arranged to PCI procedure for the chronic total occluded right coronary artery (RCA) after coronary angiography. The guide wire went through the occluded lesion and got to the distal part of the suspected "post lateral artery", which later proved to be in the right ventricle (RV). After dilating with a 2.0 mm balloon, large amount of contrast medium leaked out from the lesion; therefore, we suspected a perforation into the pericardium. Intervention: Protamine was intravenously injected to convert the effect of heparin and the 2.0 mm balloon in diameter was dilated for about 1 h to obstruct the ejected blood flow shunting into the pericardium, but the leakage persisted. Nevertheless, the patient remained stable, and we were unable to detect an effusion in the pericardium. Diagnosis: By analyzing the angiogram and echocardiogram, we found that the contrast did not leak into the pericardium, but into the right ventricle (RV) chamber. An iatrogenic coronary artery fistula (ICAF) from the RCA to the RV was confirmed. We thus terminated the procedure. Outcomes: Coronary computed tomography (CT) angiography was performed 2 days after the PCI and no abnormal shunt was found. There was no abnormal Doppler signal in the RV, either. The patient was soon discharged, and there have been no complaints of discomfort during the 10-month follow-up. Lessons: ICAFs from coronary to the RV always have favorable outcomes. Even like the one in this case that caused medium leakage could seal spontaneously without any additional management. Echocardiography or coronary CT angiography could be chosen as imaging options to follow-up ICAFs. Abstract : Supplemental Digital Content is available in the text